Tantangan Utama Pasar Modal Indonesia : Analisis Permasalahan Dan Upaya Penyelesaiannya - Advent Graceman Mendrofa; Sakti Wibowo; Dimas Darma Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Indonesian capital market faces a number of challenges that affect its growth and stability. This research analyzes the main problems facing the Indonesian capital market, such as lack of investor participation, complex regulations, and economic uncertainty. Using an analytical approach, this research also evaluates various resolution efforts that can be implemented, including investor education, regulatory simplification, and steps to increase transparency and market trust. Through this analysis, it is hoped that it can provide better insight into how to overcome the main challenges of the Indonesian capital market and improve the health and growth of the capital market for a stronger future. The results of the article explain capital market regulations, the consequences of a lack of capital market literacy, capital market risks and strategies, the role and prevention of OJK.